Social Care in Improving Self-Concept of Leprosy Patients - Hamim, Nur; Mariani, Mariani; Sismulyanto, Sismulyanto (Jurnal Ners, 2020)
ABSTRACTIntroduction: Many infectious diseases occur in developing countries with low socioeconomic conditions. One such is leprosy. Leprosy is common in developing countries as a result of the country's limited ability to provide adequate services, including among some health workers. Such health workers are lacking knowledge and understanding of the false beliefs of leprosy and its resulting disabilities. The purpose of this research is to formulate a social care model in improving self-concept of leprosy patients in Probolinggo District.Methods: This research used explanatory research survey method with a cross-sectional approach. The sample was 56  respondents. The variables were family support, social care and self-concept. The data were collected using a questionnaire modelled on  Liandi,  Richard H's concept and The Tennessee Self-Concept Scale. The data were then analyzed by Partial Least Squares (PLS)  to test the hypothesis and form the empirical model.Results: The results showed  social care was able to improve the self-concept of leprosy patients (T=5.800, T >1.96).Conclusion: Therefore, it is expected that nurses continuously  synergize in maintaining social care conditions with the community in order to improve the self-concept of leprosy patients.